DAMPAK KESEHATAN EMISI SERAT ASBES DARI CEROBONG ASAP - Mukhlis Akhadi (Energi & Kelistrikan, 2015)
Asbestos is a mineral that occurs in rock and soil, containing of magnecium-calcium-silikat fiber. Because of its fiber strength and heat resistance, asbestos has been used in a variety of building construction materials for insulation and as a fire retardant, such as heat-resistant fabrics, packaging, gaskets, and coatings, doe to its ablility whirstand in temperature up to 2.750 °C. Asbestos fibers may be released into the air by the disturbance of asbestos-containing material during product use. In general, exposure may occur only when the asbestos-containing material is disturbed or damaged in some way to release particles and fibers into the air. The severity of asbestos-related diseases, the material's extremely widespread use in many areas of life, its continuing long-term use after harmful health effects were known or suspected, and fact that asbestos-related diseases can emerge decades after exposure ceases. When materials that contain asbestos are disturbed or damaged, fibres are released into the air. When these fibres are inhaled they can cause serious diseases. This paper will describe the harmfull of asbestos emission to the environment. Mesothelioma is a cancer which affects the lining of the lungs (pleura) and the lining surrounding the lower digestive tract (peritoneum). It is almost exclusively related to asbestos exposure and by the time it is diagnosed, it is almost always fatal.